BANDAR UDARA DENGAN PENDEKATAN WAYFINDING DI PANIMBANG PANDEGLANG BANTEN - Anggraeni Budi Kusriarti; Hadi Setyawan; Edi Pramono Singgih (Universitas Sebelas Maret Surakarta, 2017)
Abstract : The designing of airport in Panimbang, Pandeglang, Banten is effected by Government plans to build infrastructure for Special Economic Region Tanjung Lesung which is located in Pandeglang Regency. Infrastructure in the form of airport to accomodate the tourists come to the tourism area in Banten especially to Special Economic Area of Tanjung Lesung. The problems that arise in the designing of the airport is how to form building design that is able to accomodate the air transport activities and meet the space requirements for the user in the form of Airport buildings by applying the concept of wayfinding at the building. The purpose of design is to meet the demands of Airport needs, functions, and user character by creating a smooth and easy-to-understand circulation and also provide convenience for the user. Wayfinding concept that is applied is the concept of the district, street concept, connector, and landmarks on the interior and exterior. The concept of planning and designing the form of the design of airport in Panimbang, Pandeglang, Banten, which served as an infrastructure for Special Economic Region Tanjung Lesung in the form of accomodation for air transportation activities that meet the needs of users in which elements of its architecture is able to create a smooth circulation by projecting the surrounding environment and the flow of events.Keywords: Architecture, Airports, Infrastructure, Circulation, Wayfinding